Perbandingan Performa Pencarian Data Berbasis Teks dengan Dan Tanpa Full-text Index pada Basis Data MySQL - Imam Thoib; Beda Puspita Candra; Nafis Sururi; Danang Satya Nugraha (Yayasan Literasi Sains Indonesia, 2024)
The amount of text-based data generated today is increasing drastically, especially with the development of digital technology and the internet. With the rapid growth of data, one of the main challenges faced is how to store and search large amounts of text-based data efficiently. This study analyzes the effect of using Full-text index in MySQL on the performance of text-based data searches, especially on large datasets. The study was conducted using a marketplace product dataset containing 2.3 million data. Testing includes searching using one, two, and three-word keywords in tables with and without full-text index. The test results show that tables with full-text index have faster search times than tables without Full-text index. Statistical analysis using the t-test produces a p value <0.05, indicating a significant effect of using Full-text index on data search efficiency. These findings confirm that full-text index is an effective solution to improve the performance of large-scale text data searches.